RANCANGAN BANGUN APLIKASI PEMBELAJARAN ONLINE (E-LEARNING) Di SMK TRITECH INFORMATIKA MEDAN BERBASIS WEB DENGAN METODE WATERFALL - Hawari Siregar; Arpan (CV. Hawari, 2025)
The rapid development of information technology has encouraged educational institutions to adopt digital-based learning systems to enhance the effectiveness of the teaching and learning process. This study aims to design and develop a web-based online learning (e-learning) application at SMK Tritech Informatika Medan using the Waterfall software development method. The application is designed to facilitate teachers and students in conducting online learning activities, such as uploading materials, submitting assignments, participating in discussions, and evaluating learning outcomes. The Waterfall method was chosen because it provides a structured and systematic approach to system development, consisting of the following phases: requirements analysis, system design, implementation, testing, and maintenance. Each phase is carried out sequentially to ensure the system’s accuracy and stability. Testing was conducted to evaluate system functionality based on user needs, including login features, user data management, uploading materials and assignments, as well as interaction through comments. The result of this study is a web-based e-learning application that can be accessed via the internet by teachers, students, and administrators. The developed system was proven to function properly during testing, with all features working as intended. This application effectively and efficiently supports the learning process and is expected to serve as an alternative solution in supporting education digitalization at SMK Tritech Informatika Medan.